Student’s Logical Reasoning Ability in Terms of Sequential Thinking Style - Pamungkas, Andini Siwi; Masduki, Masduki (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2022)
Logical reasoning ability plays an important role in serving students to understand and solves mathematical problems. The students' thinking style is one of the factors that affect the way students solve problems. This study aims to reveal the student's logical reasoning ability based on a sequential thinking style. This research used a qualitative approach with a case study design. The subjects of this study included 15 grade 8 students due to limited access during the Covid-19 pandemic. We used Gregorc's thinking style questionnaire to map students' thinking styles and three straight-line equation questions to measure students' logical reasoning abilities. Four students, two students for concrete and abstract sequential thinking styles respectively, were interviewed to further revealed their logical thinking abilities. The results showed that there were differences in students' logical thinking abilities based on differences in thinking styles on indicators of constructing and establishing assumptions, assessing and testing, establishing generalizations, and determining conclusions. Thus, it can be concluded the thinking style can affect the students' logical thinking abilities.Kemampuan penalaran logis berperan penting untuk membantu siswa memahami dan menyelesaikan permasalahan matematika. Gaya berpikir siswa merupakan salah satu faktor yang mempengaruhi cara siswa memecahkan masalah. Penelitian ini bertujuan untuk mengungkap kemampuan penalaran logis berdasarkan gaya berpikir sekuensial. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Subjek penelitian ini meliputi 15 siswa kelas VIII dikarenakan keterbatasan akses pada masa pandemi. Peneliti menggunakan angket gaya berpikir Gregorc untuk memetakan gaya berpikir siswa. Selanjutnya, peneliti menggunakan tiga soal tes materi persamaan garis lurus untuk mengetahui kemampuan penalaran logis siswa. Empat orang siswa, masing-masing dua siswa untuk gaya berpikir sekuensial konkrit dan abstrak, diwawancarai untuk menggali lebih lanjut kemampuan berpikir logis siswa. Hasil penelitian menunjukkan terdapat perbedaan kemampuan berpikir logis siswa berdasarkan perbedaan gaya bepikir sekuensial konkrit dan abstrak pada indikator membangun dan menetapkan asumsi, menilai dan menguji, menetapkan generalisasi dan menentukan kesimpulan. Dengan demikian dapat disimpulkan bahwa gaya berpikir siswa merupakan salah satu faktor yang mempengaruhi kemampuan berpikir logis siswa.